1988
DOI: 10.1227/00006123-198801010-00029
|View full text |Cite
|
Sign up to set email alerts
|

Acute subdural hematoma from ruptured posterior communicating artery aneurysm

Abstract: Acute spontaneous subdural hematoma is infrequent in association with rupture of intracranial saccular aneurysm. In the majority of cases, aneurysms of the middle cerebral artery along the convexity or of the anterior cerebral artery along the interhemispheric fissure are found to be the culprits. We present two recent cases of internal carotid-posterior communicating artery aneurysms causing acute subdural hematoma with little or no subarachnoid hemorrhage and discuss the possible mechanisms for this occurren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…[5][6][7][8][9][10][11] The three mechanisms are postulated for isolated. First, an aneurysm adherent to the arachnoid may bleed directly into the subdural space.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8][9][10][11] The three mechanisms are postulated for isolated. First, an aneurysm adherent to the arachnoid may bleed directly into the subdural space.…”
Section: Discussionmentioning
confidence: 99%
“…Third, aneurysms arising from part of carotid lying in subdural space will eventually cause SDH after rupture. 3,8 Barton and Tudor 3 studied various aneurysm locations contributing to SDH associated with aneurysmal bleed and SAH; 34.4% of SDH were due to anterior cerebral/A-Comm aneurysm bleeds. Although previous reports by Strang et al 2 in 1961 showed 17% of such cases associated with A-Comm/ anterior cerebral artery aneurysmal bleeds, the present cases exemplify the significance of aneurysmal etiology of nontraumatic SDH.…”
Section: Discussionmentioning
confidence: 99%
“…First theory: successive small bleeding or sentinel hemorrhages can cause the adhesion of the aneurysm to the adjacent arachnoid membrane, and the final rupture occurs into the subdural spaces 7 . Second theory: the stream of blood may rupture through the arachnoid membrane at some distant weak-point 12,13 . Lastly, the subdural hematoma may develop secondary to the decompression of an intracerebral hematoma into the subdural space following disruption of the arachnoid covering the cerebral cortex 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Some cases with acute unilateral SDH due to ruptured IC-PC aneurysms have been reported 3,13,19 . The adhesion of the fundus of the IC-PC aneurysm with the tentorium cerebelli should permit the extension of the hemorrhage into the subdural space without SAH 3 .…”
Section: Discussionmentioning
confidence: 99%
“…3,7,15,16,20,28) Spontaneous pure ASDH is extremely rare without common subarachnoid hemorrhage (SAH) or intracerebral hemorrhage (ICH) due to cerebral aneurysm rupture, with only 29 reported cases (Table 1). Several mechanisms have been proposed to explain the occurrence of ASDH associated with aneurysm rupture, but little definite evidence of such mechanisms is known.…”
Section: Introductionmentioning
confidence: 99%